BENEFITS OF SPIRITUALITY FOR THE ELDERLY: LITERATURE REVIEW - Lilyana, Maria Theresia Arie; Astarini, Made Indra Ayu (Nurse and Holistic Care, 2021)
Background: Aging is the final phase in the human life cycle; elderly people are at risk to face the problem as an impact loss of their roles. Objective: This study aimed to know that spirituality has an impact on providing the ability to face and accept the changes that occur with age. Methods: This literature review aimed to find out the benefits of spirituality for healthy elderly lives. Data Sources: This study searched articles published between 2010 to 2020, full-text and free articles. The search keywords consisted of “function” and “spirituality” and “elderly”. Review Methods: This literature review was conducted using analysis of the selected articles based on the inclusion criteria such full-text articles that were discussed about the benefits of spirituality for the elderly, published in the last 10 years. Result: Spirituality has an impact on influencing the incidence of depression; the main source of support for physical and psychosocial health, increasing self-awareness that they are no longer young and death will surely come for them; source of life force; coping strategies that help overcome difficult times in the elderly’s life. Conclusion: Spirituality has a positive impact on the elderly in terms of physical and mental well-being.